Legal Regulation of Procedures for Granting Land for Construction with Preliminary Agreement on the Object Location - Ekaterina Nikolaevna Malanina (Сибирское юридическое обозрение, 2011)
The article covers the acquisition of land from public ownership. The study contains detailed analysis of the procedures for the provision of land with preliminary agreement on the object location. The problems associated with deficiencies in legislation and lack of transparency, of public authorities in the provision of land give rise to corruption. The author describes the essence of legislative measures to improve this the procedure, of this provision, including the development of predominantly bankruptcy order the transfer of land to citizens and legal persons.